Keabsahan Pemberhentian Tidak Dengan Hormat Bagi PNS yang Melakukan Tindak Pidana Korupsi - Nur Tanachi Mardan; Jemmy Jefry Pietersz; Yohanes Pattinasarany (Faculty of Law Pattimura University, 2021)
Introduction: This research is motivated by Law Number 5 of 2014 concerning State Civil Servants. One of the provisions in the Law is regarding the dishonorable dismissal of civil servants. So that, the Ambon Mayor Decree Number 298 of 2019 was issued concerning for committing a criminal act of occupation or a criminal act related to his position, which was aimed at dismissing one of the civil servants within the scope of the Ambon City area.Purposes of the Research: This writing aims to identify and analyze the validity of the issuance of the Mayor of Ambon Decree Number 298 of 2019, fulfilling the validity requirements of the decision.Methods of the Research: The method used in this research is the type of normative juridical research method, the type of descriptive analytical research, the source of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Legal Material Analysis and Legal Material Analysis Methods.Results of the Research: The results show that the Ambon Mayor's Decree Number 298 of 2019 does not fulfill the legal requirements of a decision, namely the procedural aspect. So that the legal consequence is canceled or can be canceled.